Georgia : Winds of Optimism - World Bank Group (Washington, DC, 2014)
The signing of the Association Agreement with the European Union in June 2014 and the coming into effect of the Deep and Comprehensive Free Trade Area in September are landmark achievements for Georgia. The Association Agreement (AA) is focused on improvements in the areas of democracy and the rule of law, human rights, good governance, and economic development. The Deep and Comprehensive Free Trade Area (DCFTA) is likely to enhance Georgia's trade prospects and boost economic growth by enhancing the country’s export potential, especially to developed markets. This will be facilitated through improvements in quality standards and by bringing Georgia’s legislation closer to that of the European Union (EU). The DCFTA will also remove the existing barriers on the trade of goods and services with the EU. While Georgia can now export duty-free to the EU, Georgian products will have to meet certain EU requirements not only when exported but also when being consumed within the country. This marks the beginning of a long process to improve sanitary and phyto-sanitary standards, intellectual property rights protection, competition, technical regulations on industrial products, and customs and trade facilitation and this process will involve short- to medium-term costs.